2004
DOI: 10.1002/cm.20033
|View full text |Cite
|
Sign up to set email alerts
|

Direct measurement of the passive stiffness of rat sperm and implications to the mechanism of the calcium response

Abstract: Glass microprobes were used to measure the stiffness of the flagella of Triton X-100-extracted rat sperm models. The sperm models were treated with 50 microM sodium vanadate and 0.1 mM Mg-ATP to evaluate the stiffness of the passive flagellar structure without the influence of the dynein motor proteins. The passive stiffness was determined to be 4.6 (+/- 1.1) x 10(-19) N x m(2). Rat sperm models exposed to greater than 10(-5) M calcium ions exhibit a strong bend in the basal 40 microm of the flagellum, resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 46 publications
1
29
0
Order By: Relevance
“…When we measured the stiffness of bull sperm and rat sperm we found great variability from cell to cell (Schmitz- Lesich and Lindemann, 2004;Lindemann et al, 2005;Lesich et al, 2008). The variability was always most pronounced in the midpiece, the stiffest portion of the flagellum.…”
Section: How the Sperm Tail Workmentioning
confidence: 99%
“…When we measured the stiffness of bull sperm and rat sperm we found great variability from cell to cell (Schmitz- Lesich and Lindemann, 2004;Lindemann et al, 2005;Lesich et al, 2008). The variability was always most pronounced in the midpiece, the stiffest portion of the flagellum.…”
Section: How the Sperm Tail Workmentioning
confidence: 99%
“…Stiffness was measured as previously described by Schmitz-Lesich and Lindemann [2004] for rat sperm flagella. Briefly, the point of the probe tip when inducing a bend was measured and recorded.…”
Section: Stiffness Analysismentioning
confidence: 99%
“…To the best of our knowledge, a direct measurement of the lashing force and the torque generated from a trapped mammalian sperm using integrating the AFM and optical microscope system is presented here for the first time. Previous studies measuring sperm propulsive force provided statistical values for the force, for example, the stall force induced by a micro-glass probe [3][4][5] and the escape force from an optical tweezers. 6,7 The rapid movement of a sperm cell causes difficulty for force measurements.…”
Section: Resultsmentioning
confidence: 99%
“…Schmitz et al [3][4][5] reported a technique using glass needles to measure the force and the torque from the tail of a bull sperm and a rat sperm. The manual handling operation might cause the result to be less sensitive and precise.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation